The library at night - Manguel, Alberto (Yale University Press, 2008)
Inspired by the process of creating a library for his home near the Loire, in France, Alberto Manguel, writer on books and reading, has taken up the subject of libraries. "Libraries have always seemed to me pleasantly mad places, and for as long as I can remember I've been seduced by their labyrinthine logic." In this personal, deliberately unsystematic, and wide-ranging book, he offers a meditation on the meaning of libraries. Manguel, a guide of irrepressible enthusiasm, conducts a unique library tour that extends from his childhood bookshelves to the Internet, from Ancient Egypt and Greece to the Arab world, from China and Rome to Google. He ponders the personal libraries of Charles Dickens, Jorge Luis Borges, and others. He recounts stories of people who have struggled against tyranny to preserve freedom of thought, oral "memory libraries" kept alive by prisoners, libraries of banned books, and the library of books never written.--From publisher description